Cardiovascular morbidity and mortality in community-dwelling elderly individuals with calcification of the fibrous skeleton of the base of the heart and aortosclerosis (The Cardiovascular Health Study). - Barasch, Eddy; Gottdiener, John S; Marino Larsen, Emily K; Chaves, Paulo H M; Newman, Anne B (Am J Cardiol, 2006)
In the elderly, mitral annular calcification (MAC) and aortic valve sclerosis (AVS) are associated with increased cardiovascular morbidity and mortality. Aortic annular calcification (AAC) commonly occurs with MAC. However, the prognostic value of AAC, singly or in combination with MAC and AVS, for incident cardiovascular disease and mortality is unknown. From the Cardiovascular Health Study, we analyzed 3,782 participants (76 +/- 5 years of age, 60% women) who had an echocardiogram at the 1994 to 1995 examination and who were prospectively followed for an average of 6.6 years (range 0.01 to 8.5). All 3 calcification categories were associated with incident congestive heart failure (MAC: hazard ratio [HR] 1.71, 95% confidence interval [CI] 1.35 to 2.18, AAC: HR 1.62, 95% CI 1.28 to 2.06, and AVS: HR 1.50, 95% CI 1.19 to 1.89) and death. A stronger association with incident cardiovascular disease and mortality was observed with a larger number of calcification categories and with increased MAC severity. Moreover, in the participants with prevalent cardiovascular disease at echocardiographic examination (n = 1,054), MAC and AAC were still associated with cardiovascular mortality (MAC: HR 1.91, 95% CI 1.04 to 3.50; AAC: HR 2.11, 95% CI 1.16 to 3.85) even in fully adjusted models. In conclusion, MAC, AAC, and AVS are associated with a significant risk of incident congestive heart failure, cardiovascular and all-cause mortalities, and worse outcome in older patients with preexisting cardiovascular disease. Elderly patients with these findings represent a high-risk group and may require close medical attention.
Keywords: Aged; Aortic Valve; Calcinosis; Echocardiography; Female; Follow-Up Studies; Heart Failure; Heart Valve Diseases; Humans; Male; Mitral Valve; Prospective Studies; Risk Factors; Sclerosis; Severity of Illness Index; United States